PEMAHAMAN RADIKALISME AGAMA DI KALANGAN MAHASISWA STAI ALHIKMAH JAKARTA - Ekawati Ekawati; Ahmad Irfan Mufid; Gustin Gustin (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Islamic religious radicalism among students is a matter because they are a potential group that will enter various lines of life, whether as public officials, economists, entrepreneurs, educators, and so on. Furthermore, related to this, a research was conducted with the aim of research, namely to find out and analyze the understanding of STAI ALHIKMAH Jakarta students about Islamic religious radicalism. This study uses descriptive qualitative research methods. Qualitative research data collection techniques were carried out through interviews, document studies, and observations using structured instruments. Qualitative research data were analyzed using the Miles and Huberman model, namely data display, data reduction, and data tabulation. Based on that, it can be obtained the key related to Islamic religious radicalism among STAI Alhikmah Jakarta students, namely the understanding of radicalism can be seen from the pattern of social interaction which is closely related to religious procedures. Radicalism is something that has a very negative impact because it is characterized by a hard and rigid attitude. Attitude is an excessive attitude in responding to understanding in religion without attitudes in social relations. In addition, from some of these understandings, it can also be obtained that students certainly have various perceptions or understandings but still determine that radicalism has a very bad impact on the whole world, nation, and society. So that there is a need for negative literacy for students so that they do not fall into the circle of radicalism that brings the image of Islam.